Política pública de prevenç\~ao de homicídios e alternativas de aç\~ao coletiva - Tatiana Whately de Moura (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– The policy of restraining the opening hours of bars to prevent homicides, developed in south area of S\~ao Paulo, may be considered an innovating initiative giving the articulation of political actors and the alternatives used to overcome the local difficulties. This research has two general intents. First, is to contribute for debate about the elements that support the effectiveness of security policies, pointing at the difficulties and solutions founded to reduce violent crime in the area; second, analyze the institutional conditions and the behavior of actors concerning the development of collective action to promote the local public security. The co-ordinated actions of public institutions and the support of the civil society to the implementation of preventive actions represent a new way of subjugating the structural limitations that normally affects the security policies. This experience transcended the pattern of implementing policies based on coercion and repression and the positive result can only be explained by the cooperation of public, collective and individual actors involved.
Keywords: H3; 330